Motivation and its relationship to the performance of workers from a conceptual perspective - Al-Hussaini, Turkeah Salah Rashoud (Journal of Economic, Administrative and Legal Sciences, 2025)
This study investigates the relationship between employee motivation and job performance in administrative institutions, focusing on identifying the factors influencing motivation and assessing their impact on performance levels. A descriptive-analytical approach was adopted to explore the dimensions of the issue comprehensively. A structured questionnaire was developed to collect data, incorporating various metrics to evaluate motivation and correlation with key performance indicators. The survey was distributed to a random sample of 100 employees from different administrative departments within a Saudi institution.The findings revealed a strong positive correlation between high motivation levels and enhanced job performance. Both financial and non-financial incentives were found to play a critical role in boosting productivity and fostering job satisfaction. Conversely, inadequate motivational mechanisms or incentives diminished performance and heightened employee frustration.Based on these results, the study recommends implementing targeted training programs to strengthen employee motivation and increase administrative leaders' awareness of the importance of adopting comprehensive motivational strategies. Additionally, the research emphasizes the need to cultivate a positive work environment that encourages innovation and creativity, thereby supporting the achievement of organizational objectives and ensuring sustainable improvements in performance.
Keywords: Motivation; the performance of workers; employees; facilities